2010
DOI: 10.3892/or_00000966
|View full text |Cite
|
Sign up to set email alerts
|

Analogy between sphere forming ability and stemness of human hepatoma cells

Abstract: Abstract. Increasing evidence suggests that cancers contain a small subset of cancer-initiating cells, so-called cancer stem cells (CSCs) that are capable of regenerating a tumor after chemoradiation therapy. Sphere forming ability is known to be one of properties of CSCs, but the significance remains unclear. The present study focused on sphere formation of human hepatoma cells in three-dimensional culture in order to evaluate the analogy between sphere forming ability and stemness of cancer cells in vitro. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…In addition to identifying a critical role of MCU in tumor growth, we determined that MCU deletion in transformed fibroblasts diminished malignant capabilities in vitro. Our studies indicate that inhibition of MCU-mediated Ca 2+ uptake limits the ability of transformed fibroblasts to form clonally-derived spheres and invade, capabilities associated with initiation and progression of metastatic tumors (Uchida et al, 2010;Ishiguro et al, 2017), as previously observed (Tosatto et al, 2016). Previous studies have suggested a role for MCU as a promoter of invasion and metastasis in breast cancer and colorectal carcinoma-derived cell lines (Curry et al, 2013;Marchi et al, 2013;Tang et al, 2015;Cardenas et al, 2016;Tosatto et al, 2016;Ren et al, 2017;Yu et al, 2017;Liu et al, 2020).…”
Section: Discussionsupporting
confidence: 76%
“…In addition to identifying a critical role of MCU in tumor growth, we determined that MCU deletion in transformed fibroblasts diminished malignant capabilities in vitro. Our studies indicate that inhibition of MCU-mediated Ca 2+ uptake limits the ability of transformed fibroblasts to form clonally-derived spheres and invade, capabilities associated with initiation and progression of metastatic tumors (Uchida et al, 2010;Ishiguro et al, 2017), as previously observed (Tosatto et al, 2016). Previous studies have suggested a role for MCU as a promoter of invasion and metastasis in breast cancer and colorectal carcinoma-derived cell lines (Curry et al, 2013;Marchi et al, 2013;Tang et al, 2015;Cardenas et al, 2016;Tosatto et al, 2016;Ren et al, 2017;Yu et al, 2017;Liu et al, 2020).…”
Section: Discussionsupporting
confidence: 76%
“…The ability to form clonally-derived spheres on non-adherent substrates is a stem cell-like capacity related to metastatic tumor initiation and progression ( Uchida et al, 2010 ). In a sphere-formation assay, the transformed fibroblasts, but not the immortalized cells, readily formed spheres (>30 spheres per well) ( Figure 4A ), consistent with their differential abilities to form tumors in vivo ( Figure 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, there is a lack of consensus biomarkers for CSCs in HCC 24 , 29 . Consequently, the CSC subpopulation is commonly identified in HCC based on functional criteria such as their capacity to efflux Hoechst 33342 dye (side population) 30 or to form tumorspheres 31 , 32 , as only these cells have the ability to proliferate in non-adherent conditions 33 , 34 . Tumorsphere formation assay was used to isolate the CSC subpopulation of HCC cell lines.…”
Section: Resultsmentioning
confidence: 99%